Hypertension Induced Morphological and Physiological Changes in Cells of the Arterial Wall. (17th May 2018) - Martinez-Quinones, Patricia; McCarthy, Cameron G; Watts, Stephanie W; Klee, Nicole S; Komic, Amel; Calmasini, Fabiano B; Priviero, Fernanda; Warner, Alexander; Chenghao, Yu; Wenceslau, Camilla F
Abstract: Morphological and physiological changes in the vasculature have been described in the evolution and maintenance of hypertension. Hypertension-induced vascular dysfunction may present itself as a contributing, or consequential factor, to vascular remodeling caused by chronically elevated systemic arterial blood pressure. Changes in all vessel layers, from the endothelium to the perivascular adipose tissue (PVAT), have been described. This mini-review focuses on the current knowledge of the structure and function of the vessel layers, specifically muscular arteries: intima, media, adventitia, PVAT, and the cell types harbored within each vessel layer. The contributions of each cell type to vessel homeostasis and pathophysiological development of hypertension will be highlighted.